Renal replacement therapy is independently associated with a lower risk of death in patients with severe acute kidney injury treated with targeted temperature management after out-of-hospital cardiac arrest - Yoon Hee Choi; Dong Hoon Lee; Je Hyeok Oh; Jung Hee Wee; Tae Chang Jang; Seung Pill Choi; Kyu Nam Park; on behalf of the Korean Hypothermia Network Investigators (Critical Care, 2020)
Abstract Background The effect of renal replacement therapy (RRT) on the outcomes of severe acute kidney injury (AKI) after out-of-hospital cardiac arrest (OHCA) is uncertain. This study aimed to evaluate the association of RRT with 6-month mortality in patients with severe AKI treated with targeted temperature management (TTM) after OHCA. Methods This was a retrospective analysis of a prospectively collected multicentre observational cohort study that included adult OHCA patients treated with TTM across 22 hospitals in South Korea between October 2015 and December 2018. AKI was diagnosed using the Kidney Disease: Improving Global Outcomes criteria. The primary outcome was 6-month mortality and the secondary outcome was cerebral performance category (CPC) at 6 months. Multivariate Cox regression analysis was performed to define the role of RRT in stage 3 AKI. Results Among 10,426 patients with OHCA, 1373 were treated with TTM. After excluding those who died within 48 h of return of spontaneous circulation (ROSC) and those with pre-arrest chronic kidney disease, our study cohort comprised 1063 patients. AKI developed in 590 (55.5%) patients and 223 (21.0%) had stage 3 AKI. Among them, 115 (51.6%) were treated with RRT. The most common treatment modality among RRT patients was continuous renal replacement therapy (111 [96.5%]), followed by intermittent haemodialysis (4 [3.5%]). The distributions of CPC (1–5) at 6 months for the non-RRT vs. the RRT group were 3/108 (2.8%) vs. 12/115 (10.4%) for CPC 1, 0/108 (0.0%) vs. 1/115 (0.9%) for CPC 2, 1/108 (0.9%) vs. 3/115 (2.6%) for CPC 3, 6/108 (5.6%) vs. 6/115 (5.2%) for CPC 4, and 98/108 (90.7%) vs. 93/115 (80.9%) for CPC 5, respectively (P = 0.01). The RRT group had significantly lower 6-month mortality than the non-RRT group (93/115 [81%] vs. 98/108 [91%], P = 0.04). Multivariate Cox regression analyses showed that RRT was independently associated with a lower risk of death in patients with stage 3 AKI (hazard ratio, 0.569 [95% confidence interval, 0.377–0.857, P = 0.01]). Conclusion Dialysis interventions were independently associated with a lower risk of death in patients with stage 3 AKI treated with TTM after OHCA.